A Simplified Graphical Display of Production and Sales Volume Effects on Absorption Costing Income. - Stallman, James C. (The Accounting Review, 1979)
Abstract ABSTRACT: Two graphs are constructed to show (1) the effects of sales level changes on absorption costing income (at any specified production volume) and, (2) the effects of production volume changes on absorption costing income (at any specified sales level). Each construction is based on a graph of direct costing income with the result that a useful picture of the relationship between direct and absorption costing income is obtained.